CALCIUM- PHOSPHORUS METABOLISM IN THYROID DYSFUNCTION - Mariya Miteva; Maria Orbetzova; Boyan Nonchev; Deliana Davcheva (Science & Research)

(untitled)
Introduction: Thyroid dysfunction is often associated with disturbances in calcium-phosphorus metabolism, but studies on the subject provide conflicting results. Aim: To study the parameters of calcium-phosphorus metabolism in women with newly diagnosed thyroid dysfunction, not receiving specific treatment, and to compare them with those of the control group healthy women. Patients and methods: The study included 119 women with newly diagnosed thyroid dysfunction- 51 with onset of Graves’ disease and 68 with autoimmune thyroiditis. A comparison was made with the data of 75 age- matched euthyroid women. FT3, FT4, TSH, total and ionized serum calcium, inorganic phosphate, parathyroid hormone (PTH) were studied. Results: The results of the analysis showed statistically significant higher concentrations of total and ionized calcium in hyperthyroid women compared to the control group. However, no significant differences in parathyroid hormone values were found between the two groups. The comparative analysis reported a significantly higher parathyroid hormone in patients with hypothyroidism compared to euthyroid controls. Intergroup analysis revealed no differences in serum phosphorus levels. Conclusions: The observed changes in serum calcium concentrations in patients with newly diagnosed hyperthyroidism are consistent with the literature and reflect the accelerated bone metabolism in hyperthyroidism. Both hyperthyroidism and thyroid insufficiency can lead to significant disturbances in the parameters of calcium-phosphorus metabolism, requiring periodic biochemical and hormonal control.